1996
DOI: 10.1093/carcin/17.7.1451
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR EPIDEMIOLOGY AND CANCER PREVENTION: Prepubertal genistein exposure suppresses mammary cancer and enhances gland differentiation in rats

Abstract: Genistein, a component of soy, was administered to prepubertal female Sprague-Dawley CD rats and investigated for chemoprevention against mammary cancer. Genistein, at 500 microgram/g body wt or an equivalent volume of the vehicle, dimethylsulfoxide (DMSO), was injected (s.c.) on days 16, 18 and 20 post-partum. At day 50 post-partum all animals were exposed to 80 microgram dimethylbenz[a]anthracene (DMBA) per g body wt. Animals treated prepubertally with genistein as compared to DMSO had reduced incidence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
178
4
5

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 309 publications
(199 citation statements)
references
References 13 publications
12
178
4
5
Order By: Relevance
“…However, it is in agreement with another study where 3 s.c. injections of genistein to prepubertal rats had a biological effect on mammary tissue, but did not alter circulating concentrations of estradiol-17b or progesterone after puberty (Murrill et al, 1996). On the other hand, Rachon et al (2008) noted increased concentrations of estradiol and prolactin in the circulation of ovariectomized rats receiving a high dose (i.e.…”
Section: Discussionmentioning
confidence: 92%
“…However, it is in agreement with another study where 3 s.c. injections of genistein to prepubertal rats had a biological effect on mammary tissue, but did not alter circulating concentrations of estradiol-17b or progesterone after puberty (Murrill et al, 1996). On the other hand, Rachon et al (2008) noted increased concentrations of estradiol and prolactin in the circulation of ovariectomized rats receiving a high dose (i.e.…”
Section: Discussionmentioning
confidence: 92%
“…[49][50][51][52][53][54] Specifically, 3 studies have found women who consumed isoflavones during adolescence to be at lower risk for breast cancer in later life than those who did not. [52][53][54] It has also been suggested that exposure in utero or infancy through maternal soy intake or soy milk formula might influence hormone-related cancer risk in later life.…”
Section: Main Findingsmentioning
confidence: 99%
“…According to experimental (Lamartiniere et al, 1995;Murrill et al, 1996;Hilakivi-Clarke et al, 1999) and epidemiological studies (Shu et al, 2001;Wu et al, 2002), the timing of soy exposure during developmental years may be crucial for the protective effects from soy. In animals, prepubertal exposure to soy appears to be more effective than adult exposure in reducing mammary tumor formation (Lamartiniere et al, 2002).…”
Section: Introductionmentioning
confidence: 99%